Kritik Diri dan Kelenturan Psikologis pada Mahasiswa Indonesia : Implikasi Terhadap Intervensi Acceptance and Commitment Therapy (ACT) - Diana Syamila; Eka Wahyuni (Universitas Pendidikan Mandalika, 2023)
his study aims to examine the relationship between self-criticism and psychological inflexibility as a basis for ACT interventions in college students. The research method used correlation with a quantitative approach. The sample was 115 students from various universities in Indonesia. The instruments used were the Criticizing/Attacking & Self-Reassuring Scale (FSCRS) and the Acceptance and Action Questionnaire (AAQ-II). The data analysis technique used Pearson's correlation with SPSS version 20.0. The results of the research showed that there was a strong correlation with sig. 0.00 and a Pearson score of 0.757. Thus, implementing ACT, which promotes psychological flexibility, can be applied to students with a self-criticism habit.